EFFECT PERIODS QUALITATIVE FEED RATIONING IN SOME PRODUCTION TRAITS AND CARCASS TRAITS TO QUAIL JAPANESE ) Coturnix japonica ) , - Faiyz Sami AL Khatib (Mesopotamia Journal of Agriculture)
The study was conducted in the fields of agricultural research in the area of Errachidia of the Public Authority for Agricultural Research in 2012, and use the 280 Japanese quail chicks white non-naturalized one day old and has been reared free education under standard conditions until the age of 14 days, At the beginning of the third week were distributed randomly on transactions / each treatment repeating / all bis 20 chick, and included a control treatment to feed standard and the water is free on the length of the study, Transactions 2,3 and 4 were eased three levels of 10,15 and 20% Sawdust soft white, made in the early period of life during the third and fourth weeks, and has provided the above-mentioned levels of diets of transactions 5,6 and 7, respectively, in the late period of life during the fifth and sixth weeks, The results of statistical analysis as follows: The lack of significant differences within the Effect of the weight of the living body and the proportion of mortality college and increase weighing college and feed conversion ratio and carcass weight and the percentage of parts and the parts edible and the percentage of abdominal fat and dressing percentage between the two study early and late, Under the influence of levels of rationing food quality, there was no significant differences in final body weight and the increase weighted kidney and carcass traits and the proportion of abdominal fat and dressing percentage, while the proportion of mortality morally transactions rationing compared with the control except for the ratio percentages of the thighs and wings and show a significant decrease in feed consumption aggregate The conversion factor for wood shavings without food rationing transactions compared to control, Under the influence of overlap between the periods and levels of regulation differences did not note the presence of spirits in the final body weight and increase weighing college, while showing a significant decrease in feed consumption aggregate without mulch for all transactions rationing than controls, as well as the back improved significantly in feed conversion macro without mulch for the period early under the 20% level and the late period under the mitigation levels 10, 15 and 20% sawdust compared with untreated birds, Did not observe the existence of significant differences in carcass characteristics and the percentage of fat and dressing percentage of all transactions except for the study the proportion of the back.